A case of mycosis fungoides with small intestinal involvement. Issue 3 (23rd May 2019) - Nakata, Yukihiro; Suga, Hiraku; Awaji, Kentaro; Oka, Tomonori; Miyagaki, Tomomitsu; Sugaya, Makoto; Sato, Shinichi
Abstract : Mycosis fungoides is a malignant lymphoma derived from T cells. In most cases, MF presents only in the skin, although it may subsequently involve lymph nodes and other internal organs in advanced stages. Here, we report a case of MF with intestinal tract involvement.